DNA Double-Strand Breaks: A Double-Edged Sword for Trypanosomatids - da Silva, Marcelo Santos (Frontiers in Cell and Developmental Biology, 2021)
For nearly all eukaryotic cells, stochastic DNA double-strand breaks (DSBs) are one of the most deleterious types of DNA lesions. DSB processing and repair can cause sequence deletions, loss of heterozygosity, and chromosome rearrangements resulting in cell death or carcinogenesis. However, trypanosomatids (single-celled eukaryotes parasites) do not seem to follow this premise strictly. Several studies have shown that trypanosomatids depend on DSBs to perform several events of paramount importance during their life cycle. For Trypanosoma brucei, DSBs formation is associated with host immune evasion via antigenic variation. In Trypanosoma cruzi, DSBs play a crucial role in the genetic exchange, a mechanism that is still little explored but appear to be of fundamental importance for generating variability. In Leishmania spp., DSBs are necessary to generate genomic changes by gene copy number variation (CNVs), events that are essential for these organisms to overcome inhospitable conditions. As DSB repair in trypanosomatids is primarily conducted via homologous recombination (HR), most of the events associated with DSBs are HR-dependent. This review will discuss the latest findings on how trypanosomatids balance the benefits and inexorable challenges caused by DSBs.